Territorial Cohesion Trends in Portugal and Europe - Medeiros, E. (Territorial Cohesion Trends and Policies. The role of EU Cohesion Policies, 2021)
Formally included in the Lisbon Treaty (2010), alongside the longstanding concepts of economic and social cohesion, territorial cohesion is still very much a misunderstood policy concept and a difficult to achieve policy goal at the national level. Synthetically understood as a “the process of promoting a more cohesive and balanced territory, by: (i) supporting the reduction of socioeconomic territorial imbalances; (ii) promoting environmental sustainability; (iii) reinforcing and improving the territorial cooperation/ governance processes; and (iv) reinforcing and establishing a more polycentric urban system” (Medeiros, 2016), Territorial Cohesion requires a methodology which can measure its trends in a given territory, in order to be a useful policy tool. Moreover, it goes without saying that, by being a central goal for EU Cohesion Policy, at all territorial levels, there is a systematic need to assess the direct impacts of this EU Policy to achieving Territorial Cohesion trends, not only at the European level, but also at the EU Member States’ level. In this context, this ‘web conference’ intends to shed light on the potential contribution of the post-2020 EU Cohesion Policy to effectively support Territorial Cohesion trends across the European territory, and in the Portuguese territory, in particular. Alongside, in view of the recent (December 2020) approval of the new Territorial Agenda (2030), the event will also address how its proposed strategy can contribute to invert current territorial exclusion trends, and boost Territorial Cohesion trends at the national level. Finally, the discussion will be complemented by debating the role of EU regions, via the Committee of the Regions, to support Territorial Cohesion policies at all territorial levels. For this, the event will have several keynote speakers with deep knowledge on all these policy arenas, starting with the European Commissioner in charge of Cohesion Policy (Elisa Ferreira) which will debate the renovated EU Cohesion Policy strategy towards Territorial Cohesion trends. In the following, the First Vice President of the Committee of the Regions (Vasco Cordeiro) will debate the role of this EU entity to supporting territorial cohesion policies. The Portuguese Minister for Territorial Cohesion (Ana Abrunhosa) will then concentrate de debate on the instruments and Policies for a more Cohesive Territory in Portugal. This debate will be complemented by the presentation of Eduardo Medeiros focused on the Territorial Cohesion trends in Portugal and Europe. Finally, Elisa Vilares (from DG Territory) concludes the presentations by presenting The Territorial Agenda 2030 for a more balanced and cohesive territory.